Experimental investigation on ultrasonic surface rolling of Inconel 690TT. Issue 10 (27th July 2021) - Liu, Junbiao; Zhang, Xuehui; Cui, Ziyi; Yu, Jiatian; Liu, Jiang; Zou, Yangjun; Liang, Tongxiang
ABSTRACT: Inconel 690TT has an excellent high-temperature corrosion resistance and has been widely applied in steam generators of pressurized water reactor (PWR) nuclear power plants. In this paper, Inconel 690TT was investigated in the rolling reduction (RR) of the ultrasonic surface rolling process of 0, 0.2, 0.4 and 0.6 mm, respectively. It was found that the specimens with RR of 0 mm were basically equal to the untreated specimens, while the specimens with RR of 0.2 mm were the smoothest and brightest. Some cracks appeared on the surface of specimens with RR of 0.4 and 0.6 mm. Compared with 0 mm, the hardness of specimens with RR of 0.2, 0.4 and 0.6 mm increased by 187.29%, 194.51% and 200.33%, respectively. The wear resistance of specimens with RR of 0.2 mm was improved, while the wear resistance of specimens with RR of 0.4 and 0.6 mm became worse. The corresponding corrosion resistance of specimens with RR of 0.2, 0.4 and 0.6 mm was better than that of 0 mm; meanwhile, the specimen with 0.2 mm RR showed the best influence on improving the surface corrosion performance.